Speech therapy game for toddlers - Tuan Muda, Tuan Zalizam; Hamzah, Hammuzamer Irwan; Saad, Mohd Nizam; Mohamed Saufi, Aisyah Syahida; Wan Nasharuddin, Wan Nurul Hidayah (2019)
Speech delay problems are the most common disability of childhood. These children are at risk of social and academic difficulties with persisting consequences into adolescence and adulthood. Yet they are the least well detected, particularly in primary care settings. Speech delay deficits are the most common of childhood disabilities and affect about 1 in 12 children or 5% to 8% of preschool children. Early, effective and efficient speech therapy is important.The objectives of the project was to identify the main problems of speech delay, designing a speech therapy game that suitable for toddlers,develop a speech therapy game for toddlers who are having speech disorder and to evaluate the applicability and appropriateness of the speech therapy game for toddlers.The method been used was ADDIE consisting 5 phases which are Analysis, Design, Develop,Implement and Evaluate.